Economic Costs of Population Aging - Byron G. Spencer
In just over three decades all those born during the post-war baby boom will be 65 and older, and the fraction of the population ‘old’ will be far greater than previously experienced in Canada, or indeed in any modern industrial nation. That prospect has given rise to major concerns about our ability as a society to meet the large anticipated additions to health care, pension, and other costs associated with the increase in the older population. However, a balanced view requires that attention be given to all publicly provided services, not only to those services used in large measure by the elderly, and also to privately provided goods and services, since the costs must be charged against the same national income in both cases. Beyond that, it is important to recognize that population change affects not only the demand side of the economy, but also the supply side, the nation’s productive capacity. This paper reviews the literature to assess the magnitude of the prospective cost increases associated with the aging of the Canadian population and considers the practical implications for government programs and policies.